Revision of the Genus Schizoretepora (Bryozoa, Cheilostomatida) from the Atlantic-Mediterranean region - Madurell, Teresa; Spencer Jones, Mary; Zabala, Mikel (European Journal of Taxonomy, 2019)
We examined the type specimens and historical collections holding puzzling Atlantic and Mediterranean material belonging to the genus Schizoretepora Gregory, 1893. We performed a detailed study of the colonial characters and re-describe the resulting species and those that have rarely been found or have poor original descriptions. As a result of this revision, nine species are found in the northeast Atlantic and Mediterranean. Six of them are re-described and illustrated: S. aviculifera (Canu & Bassler, 1930), S. calveti d’Hondt, 1975, S. imperati (Busk, 1884), S. sp. nov.? (= S. imperati sensu O’Donoghue & de Watteville 1939) (in open nomenclature, specimen lacks ovicells), S. pungens (Canu & Bassler, 1928) and S. solanderia (Risso, 1826). For S. dentata (Calvet, 1931), no material remains; furthermore, S. hassi Harmelin, Bitar & Zibrowius, 2007 and S. serratimargo (Hincks, 1886) have recently been described and redescribed, respectively. This new arrangement attains a coherent geographical distribution: S. imperati seems restricted to the eastern Atlantic, S. dentata and S. calveti are deepwater species from Atlantic islands, S. pungens and S. aviculifera dwell on the African coasts of the Western Mediterranean, S. hassi and S. sp. nov.? (=S. imperati sensu O’Donogue & de Wateville 1939) are confined to the Eastern Mediterranean, and S. solanderia and S. serratimargo live on the European coasts of the Mediterranean.